Relationship Between Perceptions of Disease and Dieting Behavior in Hypertension Sufferers - Nakmaus Solikha; Wasisto Utomo; Nurhannifah Rizky Tampubolon (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Introduction: The factor that influences dietary behavior in hypertension sufferers is the perception of disease. This study aims to determine the relationship between perceptions of disease and dietary behavior in hypertensive patients. Methods: This study uses a correlation descriptive design with a cross sectional approach. The samples in this study were 79 respondents and were taken using a purposive sampling technique. The analysis used was bivariate analysis using the Chi-Square test. Results: The univariate results showed that the respondent was 56-65 years old, female, high school education, housewife, had suffered from hypertension for 1-3 years, had a perception that hypertension was dangerous, hypertension was a chronic disease, had complete control, hypertension treatment can help, many have severe symptoms, worry about disease, clearly understand hypertension, lack of emotional impact, and hypertension is caused by diet, stress, sleep patterns, heredity and having good dietary behavior. The results of the statistical test of disease perception with dietary behavior in hypertensive patients showed consequences (p=0.020), disease duration (p=0.540), personal control (p=0.000), treatment control (p=0.000), anxiety (p=0.000). , identity/symptoms (p=0.056), understanding of disease (p=1.000), and emotion (p=0.099). Conclusion: There is a relationship between perceptions of disease in terms of consequences, personal control, treatment control, and anxiety with dietary behavior in hypertensive patients and there is no relationship between perceptions of disease in terms of disease duration, identity/symptoms, understanding of disease, and emotions with dietary behavior in hypertension.